Una nueva especie de microteido (sauria: teiidae) del oriente de colombia (1982)
A new microteiid species is described from two sites in Colombia's Orinoco River Basin near the eastern border with Venezuela. The other Colombian Leposoma species have leaf-shaped dorsal scales, but in the new taxon they are keeled, elongate and hexagonal, with parallel lateral edges. There is a second row of small superciliary scales, and the head scales are less rugosethan in most other Leposoma species. The two other known Leposoma species with hexagonal dorsal scales L.. annectans Ruibal and L. scincoides Spix from eastern Brazil, have a longitudinally divided frontonasal scale, instead of being entire as in the new species.